The Neuroprotective Effect of MicroRNA‐22‐3p Modified Tetrahedral Framework Nucleic Acids on Damaged Retinal Neurons Via TrkB/BDNF Signaling Pathway. (25th June 2021) - Li, Jiajie; Xiao, Lirong; Yan, Naihong; Li, Yanjing; Wang, Yun; Qin, Xin; Zhao, Dan; Liu, Mengting; Li, Ni; Lin, Yunfeng
Abstract: Glaucoma is the world's leading irreversible cause of blindness. It is characterized by progressive retinal ganglion cells (RGCs) loss and axon damage, and there is no effective prevention or treatment so far. In this study, tetrahedral frame nucleic acids (tFNAs) with various biological functions are selected as the carrier, and microRNA‐22‐3p (miR‐22) are modified by attaching them onto tFNAs to synthesize a novel DNA nanocomplex (tFNAs‐miR22). Relevant results show that tFNAs can efficiently transfer miR‐22 into damaged retinal neurons to impose a neuroprotective effect on glaucoma. More interestingly, a certain synergism between tFNAs and miR‐22 is shown. tFNAs‐miR22 can selectively activate tyrosine kinase receptor B (TrkB) and regulate the TrkB‐brain‐derived growth factor (BDNF) signaling pathway to restore the expression of BDNF on the models of N‐methyl‐D‐aspartate (NMDA)‐induced glaucoma in vivo and in vitro, thus exerting the neuroprotective effect on retinal neurons. This study shows the successfully establishment of a simple but effective delivery system of microRNAs associated with glaucoma treatment, which may be a promising neuroprotective agent for future treatment of this optic neurodegenerative disease. Abstract : MicroRNA‐22‐3p (miR‐22) is modified by attaching it onto tetrahedral framework nucleic acids (tFNAs) to synthesize a novel DNA nanocomplex (tFNAs‐miR22). A simple and effective delivery system is established that can safely and quickly transfer miR‐22 into retinal neurons. tFNAs‐miR22 can reverse NMDA‐induced apoptosis of retinal neurons by regulating the TrkB‐BDNF signal pathway, thus achieving a neuroprotective effect for damaged retinal neurons.